The DNA binding affinity of HhaI methylase is increased by a single amino acid substitution in the catalytic center. - Mi, S (1993)
The HhaI methyltransferase recognizes the sequence GCGC and transfers a methyl group to C5 of the first cytosine residue. All m5C-methyltransferases contain a highly conserved sequence motif called the P-C motif. The cysteine residue of this motif is involved in catalysis by forming a covalent bond with the 6-position of cytosine prior to methyl group transfer. For the EcoRII methyltransferase, it has been shown that substitution of this catalytic cysteine by glycine is cytotoxic to E.coli cells expressing the mutant methyltransferase (Wyszynski et al. Nucl. Acids Res. 20: 319, 1992). We now show that this observation can be extended to the HhaI system and suggest that the cytotoxicity is due to abnormally tight DNA binding by the mutant methyltransferase, which probably interferes with replication or transcription.